Anthropogenic Activities and Spatio-temporal Patterns of Tropospheric NO2 over the Gandaki Province in Nepal during 2005-2020 - Sharma, Babu Ram (Prithvi Journal of Research and Innovation, 2025)
Gandaki Province is located in the mid-region of Nepal, encompassing an area of 21773 km2, which is approximately 14.66% of Nepal's total land area. The province experiences a diversity of climate variability. A massive glacier in the Himalayas is a crucial part of the freshwater and water ecosystem. Over the past two decades, anthropogenic activities within and near the boundary regions have degraded the regional ecosystem of the province. We investigate the Spatio-temporal characteristics and long-term trends derived from satellite measurements of tropospheric NO2 from the Ozone Monitoring Instrument (OMI) for the period 2005-2020. Tropospheric NO2 over the Gandaki province varies from 0.4- 0.7 x 1015 molec. cm-2 with higher values > 0.7 x 1015 molec. cm-2 over the southern region of the province and comparatively small < 0.7 x 1015 molec. cm-2 over the high-altitude region. We use a linear regression model to find the trend. There is a significant increasing trend in NO2 up to 0.1 × 1015 molec. cm–2 yr–1, with slightly higher values in the southern region of the province. The trends are seasonally more prominent in autumn (0.1 × 1015 molec. cm–2 yr–1). The main sources of NO2 in the regions are road transport, followed by agriculture. This study reveals that the high mountainous, pristine areas of the province are becoming gradually polluted due to the high anthropogenic activities within the region and the influence of nearby regions in recent years, indicating the impact of socioeconomic changes in the province.